2016
DOI: 10.1021/acs.jpclett.6b02495
|View full text |Cite
|
Sign up to set email alerts
|

“Though It Be but Little, It Is Fierce”: Excited State Engineering of Conjugated Organic Materials by Fluorination

Abstract: Fluorination is frequently used to significantly change the properties of conjugated organic materials due to fluorine's exceptional properties; well-known is its impact on electronic structure, but it also impacts the geometry despite fluorine's small size. Less known, the changes in the electronic and geometrical properties may provoke drastic changes of the excited state properties like batho- and hypsochromic shifts of absorption and emission bands (inter alia leading to excited state switching), hypo- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 126 publications
1
47
0
Order By: Relevance
“…[30,31] These oligomers all share similar properties regardless their side substituents: they possess deep-blue fluorescence, relatively high PLQE, and outstanding thermal stability with T d and T g temperatures exceeding 380 and 150 °C, respectively (see Figure S2, Supporting Information). The absorption and PL spectra of DF and DCF3 confirm that F and CF 3 fluorination lead to a moderate absorption and PL redshift, [33,34] with absorption (PL) maxima at 309 (394) nm, 309 (403) nm, and 308 (414) nm for DPHS, DF, and DCF3, respectively. The PLQE values of DF/F8BT blends, selected for a detailed study, reflect a twofold increase with respect to that of F8BT, highlighting the beneficial effects of host dilution and energy transfer.…”
mentioning
confidence: 66%
“…[30,31] These oligomers all share similar properties regardless their side substituents: they possess deep-blue fluorescence, relatively high PLQE, and outstanding thermal stability with T d and T g temperatures exceeding 380 and 150 °C, respectively (see Figure S2, Supporting Information). The absorption and PL spectra of DF and DCF3 confirm that F and CF 3 fluorination lead to a moderate absorption and PL redshift, [33,34] with absorption (PL) maxima at 309 (394) nm, 309 (403) nm, and 308 (414) nm for DPHS, DF, and DCF3, respectively. The PLQE values of DF/F8BT blends, selected for a detailed study, reflect a twofold increase with respect to that of F8BT, highlighting the beneficial effects of host dilution and energy transfer.…”
mentioning
confidence: 66%
“…20 mg (3.5 %b ased on ANTH). The 1 Ha nd 19 FNMR spectra of ANTH-6-2 ( Figure S1 in Supporting Information) demonstrated that the purity of ANTH-6-2 was 98 + mol %.…”
Section: Methodsmentioning
confidence: 99%
“…Ta ble S1 in SupportingI nformation lists all PAH(CF 3 ) n compounds reported in the literature to date (i.e.,c ompounds with at least two fused aromatic rings with 0, 1, or 2Natoms, one or more CF 3 groups, and no other substituents), including the new electron acceptors ANTH-6-2 and PYRN-6-2 reported here for the first time. The 1 Ha nd 19 FNMR spectra of ANTH-6-2 and PYRN-6-2 are shown in Figures S1 and S2, respectively.The cyclic voltammograms of ANTH-6-2, PYRN-6-2, and CORO are shown in Figure S3. The recently published UV spectra of ANTH and ANTH-6-1 are shown in Figure S4.…”
Section: General Commentsmentioning
confidence: 99%
“…12 The small atomic radius of fluorine is minimally disruptive on the structure, but the polar nature of the carbon-fluorine bond increases the dipole moment, modifies the intramolecular interactions, and potentially enhances charge transport. 13,14 Furthermore, the quadrupole moments of perfluorinated acenes are opposite in sign of the analogous acenes, thus significantly tuning the orbital energetics and intermolecular overlaps. [15][16][17] Most interestingly, fluorination has been shown to greatly impact the optical transitions of conjugated organic molecules, however, the nature of this modification varies depending on the nature of the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Most interestingly, fluorination has been shown to greatly impact the optical transitions of conjugated organic molecules, however, the nature of this modification varies depending on the nature of the molecule. 14,18 For example, in comparison to the corresponding non-fluorinated derivatives, bathochromic shifts in the absorption spectra were observed for fluorinated oligothiophenes, 19 while hypsochromic shifts were seen for oligoacenes. 12,18 In this work, we evaluated the impact of fluorine substitution on a series of benzo [1,2d:4,5-d′]bisoxazole (BBO)-based cruciforms (Chart 1).…”
Section: Introductionmentioning
confidence: 99%